Soul In Islamic Perspective (Surgery of Anatomy of the Soul from Various Perspectives) - Amin, Rizqy Mutmainnah; Ar-Rasyid , Hamzah Harun; Haeril, Haeril (Jurnal Diskursus Islam, 2024)
The purpose of writing is to find out the soul in the Qur'an and the perspectives of Muslim philosophers about the soul . The soul is defined as something in a physical form that is materially attached to human beings, visible and not hidden, but at other times it has a meaning as something in a non- material form that flows in the human body as a substance (jauhar) , spirit substance or thinking substance. In the Koran there are two terms that are often used to capture the meaning of the soul, namely ruh (spirit) and nafs . The word nafs in its various forms of derivation is found in 63 letters or 55,26 % of the total number of letters contained in the Qur'an. The word nafs has various meanings including: First, Nafs as self or someone, Second, Nafs as the self of God, Third, Nafs as spirit. Fourth, Nafs as a soul. The philosophy of the soul put forward by Muslim philosophers is an infusion of Greek philosophy which they later developed by drawing closer to Islamic teachings. According to Muslim philosophers, the soul is a spiritual substance as a place for the body. The relationship between the unity of the soul and the body is a coincidence, in which both stand alone and have different substances, so that the destruction of the body does not bring destruction to the soul. The soul remains eternally alive and will feel torment or suffering